Estudo de caso: uma reflexão sobre as estruturas internas da Secretaria de Estado de Saúde do Rio de Janeiro para acompanhamento e controle de contratos firmados com a iniciativa privada para gestão de unidades de saúde - Carlier, Ana Luiza (2015)
This study attempts to compare the internal structures of Rio de Janeiro State Public Health Secretariat (SES/RJ) organized to perform the monitoring and control of management contracts. These contracts were signed with private partners for the execution of health services in the state. The contract modalities approached were: 'Shared Management', represented by the contract signed between SES/RJ and a private company under Law no. 8.666 from June 21, 1993; and 'Social Health Organization (SHO) Management', which is a contract signed between SES/RJ and a SHO, under Law no. 6.043 from September 19, 2011. Regarding compliance with legal and regulatory milestone in relation to the control of management contracts, SES/RJ remodeled its internal organization creating new structures with that purpose. The urgency to implement new mechanisms of offering health assistance services to the state population impaired the evaluation and eventual measuring of transaction costs. Although management contracts generate the greatest public benefit, which is to offer high quality health services to the state population, the principle of efficiency expressed on Constitutional Amendment No. 19 dated 1998 must be pursued by the Public Administration. Considering Transaction Costs Economy, the hypothesis for this study is that the Public Power may incur in unknown losses due to SHO contracts governance structure if transaction costs are not measured. In order to evaluate this proposition, a comparison with the governance structure regarding Shared Management contracts is suggested.